2019
DOI: 10.1038/s41598-018-37732-y
|View full text |Cite
|
Sign up to set email alerts
|

Significant Expansion of Real-Time PCR Multiplexing with Traditional Chemistries using Amplitude Modulation

Abstract: The real time polymerase chain reaction (rtPCR) is an essential method for detecting nucleic acids that has a wide range of clinical and research applications. Current multiplexed rtPCR is capable of detecting four to six nucleic acid targets in a single sample. However, advances in clinical medicine are driving the need to measure many more targets at once. We demonstrate a novel method which significantly increases the multiplexing capability of any existing rtPCR instrument without new hardware, software, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…This primer combination was used on selected genomic DNAs from M. avium subspecies. The single DNA amplification was able to distinguish each subspecies on the basis of size by gel electrophoresis ( Figure 3 ), but can also be adapted to real time PCR using different Taqman probes and concentrations ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…This primer combination was used on selected genomic DNAs from M. avium subspecies. The single DNA amplification was able to distinguish each subspecies on the basis of size by gel electrophoresis ( Figure 3 ), but can also be adapted to real time PCR using different Taqman probes and concentrations ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…We are also the first to demonstrate multiplex RT-PCR of single cells in nanoliter droplets, greatly enhancing the capability of our platform to perform gene expression profiling of single cells and identify highly specific populations of cells. Our assay can potentially be engineered to detect more genes via further optimization and approaches such as amplitude modulation, where the relative TaqMan probe concentrations amongst targets are varied to yield distinctive PCR curves 83,84 . Since PCR primers and probes can be designed for any DNA and RNA targets, this technique can be readily adapted to analyze any cell population of interest.…”
Section: Discussionmentioning
confidence: 99%
“…This enables compatibility of the TBP assay regents with existing four- or five-channel real-time PCR instruments that are found in most clinical laboratories. The ABI 7500 Fast DX instrument was used for RT-PCR in our study; however, previous studies have demonstrated equivalent performance between ABI PCR systems and the LightCycler 480 system (Roche) (15). Thus, we find the HDPCR Tickborne Panel provides a rapid multiplexed molecular approach to identify nine pathogens or pathogen groups commonly associated with tick-borne illness in the United States and can serve as a viable adjunct for the laboratory diagnosis of tick-borne infections.…”
Section: Discussionmentioning
confidence: 99%
“…A mathematical algorithm is used to analyze raw RT-PCR amplification data (PCR curves) to identify and differentiate up to six unique targets per real-time PCR fluorometric channel. This HDPCR approach has previously been applied to successfully identify nine viral agents in simulated nasopharyngeal specimens across a wide concentration of 10 1 to 10 5 genomic copies/PCR (15). Single channel multiplexing allows expansion of multiplex capabilities enabling identification of the nine TBP assay targets and an internal control using just four channels of a standard real-time PCR instrument (Fig.…”
Section: Introductionmentioning
confidence: 99%